2021
DOI: 10.1007/s11483-021-09706-7
|View full text |Cite
|
Sign up to set email alerts
|

Digestive and Physicochemical Properties of Small Granular Starch from Euryale ferox Seeds Growing in Yugan of China

Abstract: In this study, the morphological, physicochemical and digestibility properties of Yugan Euryale ferox seeds starch (Y-EFS) were comprehensively analyzed. The results showed that Y-EFS contained 45.85% amylose. These starch granules of Y-EFS appeared as irregular polyhedron shape with smooth surface and relatively uniform size around 2.29 μm. The determined average molecular weight of Y-EFS were 1.85 × 10 5 and 3.00 × 10 3 Da, respectively. X-ray diffraction verified that Y-EFS was a typical A-type starch with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…The sieved slurry was used to separate and purify EFS according to our previous reported experimental method. 19…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sieved slurry was used to separate and purify EFS according to our previous reported experimental method. 19…”
Section: Methodsmentioning
confidence: 99%
“…The slurry was sieved through a 60‐mesh sieve to remove the EFCs, which were further dried at 40 °C for the extraction of phenolics. The sieved slurry was used to separate and purify EFS according to our previous reported experimental method 19 …”
Section: Methodsmentioning
confidence: 99%
“…The A‐type starch proving that E. ferox seed had a significantly high crystallinity and bigger crystallization area. E. ferox seeds also had a relatively high temperature and gelatinization enthalpy (Zhang et al, 2022). The crude polysaccharides were extracted from E. ferox by different methods.…”
Section: Major Bioactive Compounds Of E Feroxmentioning
confidence: 99%
“…10 High percentages of butylated hydroxytoluene, linoleic acid, and tocopherols are found in the essential oil of fox nut and they exhibit a significant amount of scavenging activity. 11 So far, fox nut starch has been studied for its physicochemical properties, 12 as a slowly digestible starch for its processing and digestive properties, 13 as a resistant starch, 14 and as an octenyl succinic anhydride (OSA)-modified starch for stabilizing Pickering emulsions. 15 However, as far as the authors are aware, no work has been reported in the literature on the acetylation of unpopped fox nut starch to the degree of acetylation authorized by FDA for food applications.…”
Section: Introductionmentioning
confidence: 99%
“…So far, fox nut starch has been studied for its physicochemical properties, 12 as a slowly digestible starch for its processing and digestive properties, 13 as a resistant starch, 14 and as an octenyl succinic anhydride (OSA)‐modified starch for stabilizing Pickering emulsions 15…”
Section: Introductionmentioning
confidence: 99%